Fatigue Resistance of High-Thickness Al-Alloy Sheets after Water Jet Cutting - Ivo Cerny; Dagmar Mikulova (Communications - Scientific letters of the University of Zilina, 2009)
Water jet cutting is a useful advanced technology of separating materials with a great industrial potential due to high cutting speed, precision, shape repeatability and possibilities to be performed automatically with a computer control. It is well known, however, that fatigue properties are particularly strongly affected by surface conditions and quality of surface layer. Water jet cutting was applied to Al-alloy sheets of fairly high thickness, namely 50.8 mm. Fatigue resistance of water cut specimens and failure mechanisms were investigated and compared with those studied using a reference batch of specimens manufactured by fine milling. Character of surface damage caused by water jet cutting resulted in a considerable reduction of fatigue strength in comparison with milled surface. The results are discussed considering microscopic analysis of surface and subsurface conditions of fatigue crack initiation.